2205. Mandatory Infectious Diseases or Hepatology Consult to Improve HCV Linkage to Care in the Inpatient Setting. (26th November 2018) - Ingilizova, Marinela; Coppock, Dagan; Szep, Zsofia; D'Mello, Kevin; Kesaris, Anna; Scott, Tiffany; Franks, Taneesa; Chou, Edgar; Lee, Dong Heun
Abstract: Background: At Hahnemann University Hospital, the prevalence of hepatitis C virus (HCV) infection is close to 17%, which is much higher than the estimated 2% prevalence in the United States general population. However, linkage to care from an inpatient setting is historically lower than for those diagnosed with HCV infection in the outpatient setting. In the era of effective HCV treatment, improving linkage to care is an essential step to cure HCV infection. Here we describe the impact of mandatory HCV consults on the success of linkage to care. Methods: We performed a retrospective observational study of HCV patients who tested positive for HCV from July 2017 to December 2017 and were born between 1945 and 1965 at Hahnemann University Hospital, Philadelphia, PA. Once a patient was identified as having chronic HCV infection, either the Infectious Disease or Hepatology team evaluated the patient and an HCV navigator facilitated linkage to care. We defined linkage as a patient subsequently being seen at the Outpatient Hepatology Clinic or Infectious Disease Clinic within 3 months of discharge from the hospital. Results: Among 524 Baby Boomers tested, 106 (20%) had positive HCV antibody tests. Sixty-nine (65%) had chronic HCV infection and 7(9%) were already linked to care. Among 62 patients, 24 (39%) had an infectious disease (ID) or Hepatology consult. Patients who were seen by a consultant were more likely to be linked to care within 3 months (50% vs. Twenty-two%, P = 0.016). One of the main barriers that a consultant did not see a patient was that confirmatory HCV viral load result was not available at the time of discharge. If the viral load was available prior to discharge, a patient was more likely seen by a consultant. (54% vs. 7%, P < 0.0001) Conclusion: Mandatory HCV consults in the inpatient setting improved linkage to care for HCV-infected patients. One of the main barriers of HCV mandatory consults was HCV viral load result not being available at the time of discharge. In the era of effective direct-acting antiviral treatment, mandatory HCV consults should be implemented to improve the rate of linkage to care. Early routine lab testing for HCV antibody during a hospitalization and timely availability of results will be crucial to the success of such an intervention. Disclosures: All authors: No reported disclosures.